Growth Response of Clove (Syzygium aromaticum L.) Seedlings to Different Light and Water Regimes - Adi Setiawan; Satoshi Ito; Yasushi Mitsuda; Ryoko Hirata; Kiwamu Yamagishi; Yasa Palaguna Umar (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2021)
The growth responses of clove seedling to light and soil water regimes were studied by a field experiment with shading and irrigation treatments to clarify their growth traits at the early stage of plantation establishment. Eighteen-month-old clove seedlings were subjected to twelve treatments, that is, 3 shading treatments (0%, 60% and 80% shading) × 4 watering treatments (1.0, 0.75, 0.5 and 0.25 l/m2 /day), for ca. 6 months. Increment ratio of seedling height (IH), number of newly created buds (NB) during the experimental period and dry mass per plant at the end of the experiment (leaves: LM, stem and branch: SM, root: RM and total plant: TM) were compared among the treatment. The growth of clove seedlings (height < 150 cm) was generally more susceptible to water stress than to low light availability. The growth retardation by water shortage was observed in all the examined parameters except for SM. The effect of the shading treatment appeared to be limited; however, LM and NB showed significantly lower values under the heavy shade (80% shading). We concluded that dense planting of clove seedling with other competitive crops should be avoided to ensure the fast growth of clove seedlings at the establishment stage.